Extraction of essential oils from Zingiberaceace famili by using Solvent-free Microwave Extraction (SFME), Microwave-assisted Extraction (MAE) and hydrodistillation (HD) - Abd Aziz, Nor Azila; Hassan, Jumiah; Osman, Nurul Huda; Abbas, Zulkifly (Asian Online Journals, 2017)
Solvent-free microwave extraction (SFME) and microwave-assisted extraction (MAE) is a combination of dry and wet distillation with microwave heating. Both methods were compared with hydrodistillation (HD) for the extraction of essential oil from three types of rhizomes in Zingibereaceace family: Mango ginger (Curcuma amada), Java turmeric (Curcuma xanthorrhiza Roxb), and Black turmeric (Curcuma aeruginosa). Better results were obtained with SFME and MAE in terms of rapidity with 1 h extraction time using SFME and MAE vs. 4 h of extraction time using HD. SFME and MAE gives highest yield of essential oils at every second during the extraction process compared with HD.